Penerapan Teknik Token Ekonomi untuk Mengurangi Prokrastinasi Akademik: Sebuah Studi Meta-Analisis - Indreswari, Henny; Aliyah, Shabrina Muyassirotul (Buletin Konseling Inovatif, 2025)
The habit of academic procrastination can occur when students have poor time management in studying and completing assignments. One technique school counselors can use to overcome this procrastination behavior is the token economy technique. Several previous studies have proven the effectiveness of this technique in reducing academic procrastination behavior. This research further evaluates the effectiveness of the token economy technique in reducing academic procrastination behavior in students. The method used in this research is meta-analysis, where data is taken from previous articles using coding worksheets as a research instrument. Data analysis was performed using the paired sample T-test and effect size calculations using Cohen's d formula. The results of the Paired Samples Test obtained a significance value of 0.048 less than 0.05, indicating that token economy techniques can be used to reduce academic procrastination behavior in students. Even so, the results of the effect size test using Cohen's d formula obtained a value of 0.43 which is included in the small category. Thus it can be concluded that the use of economic token techniques has a negligible effect on reducing academic procrastination behavior in students.